Service Innovation Accelerates the Issuance of Population Documents for Displaced Persons in Pekanbaru City - Fitri Diana; Adianto Adianto (FISIP Universitas Malikussaleh, 2023)
Service innovation provided by the Regional Government through the Population and Civil Registration Service are breakthroughts in public services which are creative idea and modification that are able to provide benefits to the community. Through Disdukcapil, the government provides population administration services in recording e-KTP to the public. One of the Disdukcapil that provides population administration services is Pekanbaru City Disdukcapil through the Sipintar Innovation (Service System to Complete the Identity of Displaced Persons). The purpose of this study was to determine the implementation of Sipintar innovation in Pekanbaru City Disdukcapil and identify factors that hinder the implementation of Sipintar innovation. This research uses bugge's theory of innovation success attributes in Winda (2021), where there are six indicators, namely: Governance and Innovation, Sources of the Ideas for Innovation, Innovation Culture, Capabilities and Tools, Objectives, Outcomes, Expense and Obstacles, Collecting Innovation Data for Single Innovation. This type of research is qualitative research with a phenomenological approach. The collection of necessary data, both primary and secondary data, is collected through interviews, observations, documentation, then analyzed so that conclusions can be drawn from existing research problems. The result of this study is that the existing innovations have not been optimally implemented because there are still inhibiting factors in its implementation, namely the low socialization of face-to-face / direct innovations, the limitations of e-KTP recording devices, and also network disruptions when recording e-KTP.Inovasi pelayanan yang diberikan Pemerintah Daerah melalui Dinas Kependudukan dan Pencatatan Sipil merupakan terobosan dalam pelayanan publik yang merupakan ide kreatif maupun modifikasi yang mampu memberikan manfaat kepada masyarakat. Melalui Disdukcapil pemerintah memberikan layanan administrasi kependudukan dalam perekaman e-KTP kepada masyarakat. Salah satu Disdukcapil yang memberikan pelayanan administrasi kependudukan adalah Disdukcapil Kota Pekanbaru melalui Inovasi Sipintar (Sistem Pelayanan Untuk Melengkapi Identitas Orang Terlantar). Tujuan penelitian ini adalah untuk mengetahui pelaksanaan inovasi Sipintar di Disdukcapil Kota Pekanbaru dan mengidentifikasi faktor yang menghambat pelaksanaan inovasi Sipintar. Penelitian ini menggunakan teori atribut keberhasilan inovasi oleh Bugge dalam Winda (2021), yang mana terdapat enam indikator, yaitu: Governance and Innovation, Sources of the Ideas for Innovation, Innovation Culture, Capabilities and Tools, Objectives, Outcomes, Expense and Obstacles, Collecting Innovation Data For Single Innovation. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan fenomenologi. Pengumpulan data-data yang diperlukan baik data primer maupun sekunder dikumpulkan melalui wawancara, observasi, dokumentasi, kemudian dianalisis sehingga dapat ditarik kesimpulan dari masalah penelitian yang ada. Hasil penelitian ini adalah inovasi yang ada belum optimal dilaksanakan karena masih terdapat faktor penghambat dalam pelaksanaannya yaitu rendahnya sosialisasi inovasi secara tatap muka/langsung, keterbatasan alat perekam e-KTP, dan juga adanya gangguan jaringan saat melakukan perekaman e-KTP.